Efficiency loss and uniform-price mechanism - Karpowicz, M.; Malinowski, K. (2008 47th IEEE Conference on Decision and Control, 2008)
We investigate the properties of the class of resource allocation mechanisms with uniform pricing scheme. An important consequence of the assumption that agents maximize their profits is that both the resource price and the quantities assigned to agents can be viewed as the implicit functions of the messages communicated to the mechanism. As a result agents¿ individual decisions become interdependent, which makes each agent capable of anticipating the effects of individual actions on the price of the resource. Focusing our attention on the Nash equilibrium solution concept we discuss the efficiency of equilibrium allocations of the game defined by the allocation mechanism both from the perspective of the global system goals and the individual objectives of agents. Our first contribution is the ranking of three variations of the uniform-price mechanism. We demonstrate the significant role of strategic variables used by agents and analyze mechanism designer¿s best response to agents¿ expected price-anticipating behavior. Since the resource allocation model being subject to our considerations can very well serve as a description of the uniform-price auction for divisible resources, the results of this paper can be viewed as an inquiry into properties of this auction format. As a second contribution we show how signals exchanged between agents and the mechanism can be successfully used to reach an equilibrium point in an iterative bidding process.